Diet contributes to urban-induced alterations in gut microbiota: experimental evidence from a wild passerine - Aimeric Teyssier; Erik Matthysen; Noraine Salleh Hudin; Liesbeth De Neve; Joël White; Luc Lens (PANGAEA, 2019)
Urban sprawl increasingly affects the ecology of natural populations, including host- microbiota interactions, with observed differences in the gut microbiota between urban and rural hosts. While different mechanisms could explain this pattern, dietary uptake constitutes a likely candidate. To assess the contribution of diet in explaining urban–rural variation in gut microbiota, we performed an aviary experiment in which urban and rural house sparrows where fed with mimics of urban or rural diets. Before the experiment, rural sparrows hosted more diverse gut communities, with a higher relative abundance of Enteroccocaceae and Staphylococcaceae and lower abundance of genes involved in xenobiotic degradation and lipid metabolism than their urban counterparts. The experimental diets significantly altered gut microbiota alpha- and beta-diversity and taxonomic composition, with the strongest shifts occurring in individuals exposed to contrasting diets. Overall, diet-induced shifts resembled initial differences between free-ranging urban and rural hosts. Furthermore, rural diet had a positive impact on urban host body mass but only in hosts with the highest initial gut diversity. Overall, our results indicate that diet constitutes a major factor contributing to differences in gut microbiota along the urbanisation gradient and provide new insights on possible fitness consequences of a reduced gut diversity in urban settings.